2001
DOI: 10.1210/endo.142.11.8484
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Stimulates Catecholamine Synthesis in a PKC-Dependent Manner in Cultured Porcine Adrenal Medullary Chromaffin Cells

Abstract: We have previously shown that murine recombinant leptin directly stimulates catecholamine synthesis through the long form of the leptin receptor (Ob-Rb) expressed in cultured porcine chromaffin cells. Additionally, we found that leptin activates IP3 production after PLC activation. It is well established that activation of PLC elicits IP3 production as well as an increase in diacylglycerol, a compound that stimulates PKC. Therefore, we investigated the involvement of PKC in leptin-induced catecholamine synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…In accordance with the results of Takekoshi et al (45) in chromaffin cells, we found that leptin enhances the expression of PKC -␣, -␤ I , -␤ II , and -␥ in macrophages. To the best of our knowledge, this is the first report that leptin activates PKC in vascular cells.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the results of Takekoshi et al (45) in chromaffin cells, we found that leptin enhances the expression of PKC -␣, -␤ I , -␤ II , and -␥ in macrophages. To the best of our knowledge, this is the first report that leptin activates PKC in vascular cells.…”
Section: Discussionsupporting
confidence: 93%
“…5C). Leptin has been reported to trigger PKC activation and elicit PKC-dependent ERK1/2 phosphorylation in peripheral cells (25). Application of the PKC inhibitor GF109203X (1 M) (26) did not significantly affect leptinmediated rise in phospho-ERK1/2 in cortical neurons (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Also in rat adrenal zona glomerulosa cells ERK1/2 activation blocked cell proliferation and stimulated steroidogenesis (Otis et al 2005, Otis & Gallo-Payet 2007. A role of ERK1/2 for functional aspects of cortical ( Wu et al 2002, Chang et al 2008 or medullary cells (Cox & Parsons 1997, Takekoshi et al 2001, Shibuya et al 2002, Yanagihara et al 2005, Shinkai et al 2007) has also been provided by others. In addition to growth and function also migration is under control by ERK1/2 in adrenomedullary cells (Ho et al 2001(Ho et al , 2005.…”
Section: Intracellular Control Of Adrenal Growthmentioning
confidence: 87%